Działalność kulturalna ochotniczych straży pożarnych na tle innych kierunków aktywności - Behr, Jolanta; Bigos, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Volunteer fire brigades are fire protection units. They are intended primarily for the fight against fires, natural disasters and other local threats. An important area of their activity is also the organisation and conduct of cultural activities. The aim of the study is to analyze the forms and scope of this activity and to determine its role in the functioning of local government communities.
Keywords: działalność kulturalna; ochotnicze straże pożarne; społeczności lokalne; formy i zakres działania